Qana’ah sebagai Faktor Moderasi dalam Perilaku Konsumsi Makanan dan Minuman Kemasan Multi Trip di Kalangan Pelajar - muhammad adnan; Abd. Rasyid R; Ismail Keri (Jurnal Ekonomi dan Bisnis Digital, 2025)
AbstractThe lifestyle shift among students in the digital era has driven a growing trend in the consumption of multi-trip packaged food and beverages. This study highlights the influence of environmental awareness, consumption compliance, and price on this consumption change, while also exploring the moderating role of qana’ah (Islamic contentment). The central focus is on how the Islamic value of qana’ah can help balance students’ consumer behavior to be more environmentally friendly and sustainable. The objective of this research is to examine whether environmental awareness, consumption compliance, and price significantly influence consumption change, and to what extent qana’ah moderates these relationships. This study adopts a quantitative approach using a survey method. Data were collected through questionnaires distributed to 150 students in Bone Regency and analyzed using Structural Equation Modeling (SEM) with the SmartPLS application. The results show that environmental awareness does not have a significant effect, while consumption compliance and price have a significant effect on the shift toward multi-trip packaging consumption. Moreover, qana’ah does not moderate the effects of environmental awareness and consumption compliance, but significantly moderates the effect of price. The implications of this research suggest that applying the value of qana’ah can be an effective strategy to foster sustainable consumption awareness among students. These findings are valuable for policymakers, educators, and packaging industry stakeholders in developing more ethical and ecological approaches. Keywords: Qana’ah, multi-trip packaging consumption, environmental awareness, consumption compliance, price